2015
DOI: 10.1088/0031-9155/61/1/183
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm for the calculation of physical and biological irradiation quantities in scanned ion beam therapy: the beamlet superposition approach

Abstract: The calculation algorithm of a modern treatment planning system for ion-beam radiotherapy should ideally be able to deal with different ion species (e.g. protons and carbon ions), to provide relative biological effectiveness (RBE) evaluations and to describe different beam lines. In this work we propose a new approach for ion irradiation outcomes computations, the beamlet superposition (BS) model, which satisfies these requirements. This model applies and extends the concepts of previous fluence-weighted penci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 47 publications
(54 reference statements)
0
34
0
Order By: Relevance
“…Secondly, these quantities have been used to create two 3D physical dose maps, one for the prescription and one for measured data, by using a validated dose computation software. 12 The correspondence of the two dose distributions has been evaluated with the gamma-index method using a 2 mm grid spacing with 0.2 mm resolution, 2 mm distance-toagreement (DTA) and 2% dose difference. 13 The analysis of the maximum gamma value and of the percentage of points with gamma ≤ 1 (passing volume, in the following) was performed as a function of the day of the treatment.…”
Section: E Analysis Of the Treatment Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, these quantities have been used to create two 3D physical dose maps, one for the prescription and one for measured data, by using a validated dose computation software. 12 The correspondence of the two dose distributions has been evaluated with the gamma-index method using a 2 mm grid spacing with 0.2 mm resolution, 2 mm distance-toagreement (DTA) and 2% dose difference. 13 The analysis of the maximum gamma value and of the percentage of points with gamma ≤ 1 (passing volume, in the following) was performed as a function of the day of the treatment.…”
Section: E Analysis Of the Treatment Fieldsmentioning
confidence: 99%
“…To evaluate the impact on dose distributions of deviations between prescribed and measured quantities, TPS reference values and corresponding values measured by monitor chambers were used as input of a validated dose calculation tool. 12 The correspondence between the 3D dose maps has been quantified by means of the gamma-index criterion, 13 and the results have been reported for one representative patient treated with protons. Finally, to study the effect on delivery quality of the implementation of a feedback algorithm for the correction of small position deviations, delivered dose distributions of the same treatment plans before and after feedback implementation have been compared.…”
Section: Introductionmentioning
confidence: 99%
“…It exploits the duty cycle of the CNAO synchrotron, which has a spill of 1 second and a dead time of 3-4 seconds during which RIDOS is able to evaluate a fast forward planning and a fast gamma index [33] to compare the actual delivered dose with the original planning. This is made by a deep exploitation of the graphic processing unit (GPU) calculation, which allows, in our case, to gain a factor 800 with respect to the existing single core CPU calculation [34]. Moreover, RIDOS is also able to manage the patient 4D-CT together with the information of the real-time respiratory phase, in order to account for intra-fraction target deformation.…”
Section: Pos(inpc2016)123mentioning
confidence: 99%
“…These studies showed that scintillator‐based dosimetry systems offered a fast response and could be used as high‐resolution dosimeter tools if the quenching effects were corrected. A commercially available scintillator‐based dosimeter tool, Lynx (IBA Dosimetry, Louvain‐la‐Neuve, Belgium), has been used in proton beam measurements . The Lynx detector is suitable for 2D relative dosimetry in ion beams with short‐term stability, dose linearity, and good image quality.…”
Section: Introductionmentioning
confidence: 99%
“…A commercially available scintillator-based dosimeter tool, Lynx (IBA Dosimetry, Louvain-la-Neuve, Belgium), has been used in proton beam measurements. [31][32][33] The Lynx detector is suitable for 2D relative dosimetry in ion beams with short-term stability, dose linearity, and good image quality. Although these detectors are suitable for ordinary proton QA, they cannot be used to monitor patient treatment because they are too bulky to place between the patient and the nozzle.…”
Section: Introductionmentioning
confidence: 99%